Prevalence of Methicillin Resistant Staphylococcus Aureus (MRSA) in Surgical Site Infections in a Tertiary Care Hospital - Hussain, Shagufta; Shams, Rabia; Ahmad, Khurshid; Perveen, Roshan; Riaz, Bushra (International Journal of Pathology, 2018)
Objective: To determine the prevalence of Methicillin Resistant Staphylococcus aureus (MRSA) in post-operativewound infections in surgical wards and surgical ICU and also to define the antimicrobial susceptibility pattern of thestrains isolated.Design: A cross sectional prospective study.Place and Duration of Study: Departments of Pathology and Surgery, Pakistan Institute of Medical Sciences (PIMS),Islamabad, Pakistan. January 2004 to August 2005.Patients and Methods: Wound swabs from patients who had undergone surgery and were suspected of havingpostoperative infection of the wounds were collected and inoculated on blood agar and MacConkey agar plates. Afterincubation for 24-48 hours, plates were examined for the growth of S. aureus. Anti-microbial susceptibility testwas performed using oxacillin 1ug disc to detect methicillin resistance. An inhibition zone = or <10mm was taken asindicative of MRSA.Results: A total of 1310 surgical wound swabs yielded growth of bacterial pathogens out of which 273 (20%) were found tobe S. aureus. 225 of the affected patients were admitted in surgical wards and 48 in SICU. Analysis of the antimicrobialsusceptibility patterns of the isolates revealed that 105 (39%) were strains of Methicillin Resistant Staphylococcus aureus(MRSA) as indicated by their resistance to Oxacillin (1ug disc). Significantly higher proportion of the MRSA isolates werefrom SICU, 31/48 – 65% than from the surgical wards, 74/225 – 35% (p < 0.05) indicating the inherent tendency of thesestrains to become endemic in the critical care units as well as their propensity for nosocomial spread. Susceptibility patternsfurther revealed that Vancomycin and Teicoplanin were the most effective antimicrobial agents for MRSA infections - 100%of the strains being fully susceptible – followed by Fusidic acid (80% susceptible). The reverse was true as regards theefficacy of Gentamicin and Ciprofloxacin, to which 100% of the isolates were resistant. Other antibiotics yielded variableresults.Conclusions: 273 (20%) out of 1310 post-operative wound infections were caused by S. aureus, 105 (39%) were strainsof MRSA whose prevalence was found to be significantly higher in surgical ICU than in the surgical wards (65% ascompared to 35% respectively –p < 0.05). All the isolates were found to be susceptible to Vancomycin. It is concluded thatMRSA is a serious nosocomial pathogen in surgical site infections and requires strict intervention for its preventionand control